Immune markers in oral discomfort patients before and after elimination of oral galvanism - Podzimek, Stepan; Tomka, Milan; Sommerova, Pavla; Lyuya-Mi, Yelena; Bartova, Jirina; Prochazkova, Jarmila (Neuro endocrinology letters, 2013)
BACKGROUND: An enhanced release of metals in the mouth due to galvanic cell formation is considered to be one of the causes of oral discomfort. The aim of this study was to investigate the influence of galvanic cell on salivary immune defense factors. MATERIAL AND METHODS: The levels of IgA1, IgA2, sIgA, lysozyme and antiIgA/HSP60 were evaluated in representative samples from 159 patients with galvanism, from 177 patients without galvanism and in two control groups. All the participants underwent personal history taking, clinical examination, galvanic currents measurement and saliva collection. RESULTS: Electro active dental materials were removed in 30 patients. There was a significant increase in IgA2 level, a significant decrease in antiIgA/HSP60 levels and an increase in IgA1, sIgA and lysozyme levels found after the removal of electro active restorations. Morphological symptoms disappeared in 70% of the treated patients. CONCLUSION: The study confirmed that pathologic galvanic phenomena influences the immune defense reactions in the oral cavity and thus may cause the symptoms of oral discomfort. A measurement of the galvanism and a subsequent removal of electro active restorations should become a common therapeutic procedure in the patients with oral discomfort.
Keywords: Device Removal; Dental Restoration, Permanent; Mouth; Adult; Male; chaperon hsp60; lidé; Humans; Immunoglobulin A; elektrogalvanismus intraorální; Biomarkers; muramidasa; odstranění implantátu; Saliva; trvalá zubní náhrada; Metals; mužské pohlaví; mitochondriální proteiny; ústa; imunoglobulin A; sliny; dospělí; kovy; Electrogalvanism, Intraoral; Muramidase; biologické markery; ženské pohlaví; Mitochondrial Proteins; Female; Antibodies, Anti-Idiotypic; Chaperonin 60; protilátky anti-idiotypické